5(x-5)+2(-4x+8)=-3x+13

Simple and best practice solution for 5(x-5)+2(-4x+8)=-3x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-5)+2(-4x+8)=-3x+13 equation:


Simplifying
5(x + -5) + 2(-4x + 8) = -3x + 13

Reorder the terms:
5(-5 + x) + 2(-4x + 8) = -3x + 13
(-5 * 5 + x * 5) + 2(-4x + 8) = -3x + 13
(-25 + 5x) + 2(-4x + 8) = -3x + 13

Reorder the terms:
-25 + 5x + 2(8 + -4x) = -3x + 13
-25 + 5x + (8 * 2 + -4x * 2) = -3x + 13
-25 + 5x + (16 + -8x) = -3x + 13

Reorder the terms:
-25 + 16 + 5x + -8x = -3x + 13

Combine like terms: -25 + 16 = -9
-9 + 5x + -8x = -3x + 13

Combine like terms: 5x + -8x = -3x
-9 + -3x = -3x + 13

Reorder the terms:
-9 + -3x = 13 + -3x

Add '3x' to each side of the equation.
-9 + -3x + 3x = 13 + -3x + 3x

Combine like terms: -3x + 3x = 0
-9 + 0 = 13 + -3x + 3x
-9 = 13 + -3x + 3x

Combine like terms: -3x + 3x = 0
-9 = 13 + 0
-9 = 13

Solving
-9 = 13

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -3q^2+14q+49=0 | | 9x^3y^8z^17/-3x^5y^5z^10 | | -4(4x+1)=-116 | | -4x+3x-4=0 | | 7/x-1=0 | | -216=-6(4a+8) | | 2x-7=10x+8 | | -35+y=-12 | | 8m=m+35 | | -12t=-108 | | 12-v=45 | | X-27=59 | | a(n)=-4n+13 | | 10+y=79 | | 2x^2+32x=72 | | 6(3b+2)+2=b-20 | | X/2*30=1000 | | -6+12x=102 | | 5x^2+5y^2-6x-6y+5=0 | | -27+8=-12+c+20 | | 54b+72=252 | | -14+x=-22 | | [v-3]=-7 | | 8b+4=92 | | -83=4(1-4b)-7 | | 6+3x=6-6x | | -13c+7=-32 | | -3(x-8)=5(x+8) | | -7(2n-2)+2=100 | | 8y-12=52 | | 37+5=35+7 | | (f+9)=39 |

Equations solver categories